2020
DOI: 10.1155/2020/9063929
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Emission Experimental Research of the Damage Characteristics of Raw Coal under Different Loading and Unloading Rates

Abstract: In this study, triaxial load failure experiments of coal samples under different strain rates and different confining pressure unloading rates were carried out using an RTX-1000 rock triaxial apparatus, and the acoustic emission characteristic parameters of a Micro-II acoustic emission imaging acquisition instrument were used to study the acoustic emission characteristics and damage deformation law of coals under different conditions. Damage models were constructed on the basis of the characteristic parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The slip lines resulted from high dislocation motion under the applied stress. Q235 steel is a polycrystalline material whose deformation is achieved by the gradual movement of crystals along the slip surface (Zhang et al, 2015). More slip lines were found when the applied load increased or closer to the hardening stage at 514 s, as shown in Fig.…”
Section: Optical Microscopy Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…The slip lines resulted from high dislocation motion under the applied stress. Q235 steel is a polycrystalline material whose deformation is achieved by the gradual movement of crystals along the slip surface (Zhang et al, 2015). More slip lines were found when the applied load increased or closer to the hardening stage at 514 s, as shown in Fig.…”
Section: Optical Microscopy Analysismentioning
confidence: 97%
“…AE signals are generated from material damages such as twining, dislocation, cavitation, and crystal slip (Heiple, Carpenter, 1987;Bohlen et al, 2004;Trojanová et al, 2010). Previous work has shown that the damage response of Q235B steel can be assessed by the AE method (Zhang et al, 2015) and the defects can be located accurately (Wu et al, 2008;Jiang, Xu, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…e fuzzy analytic hierarchy process is a systematic analysis method combining qualitative and quantitative analysis. It is a comprehensive application of the analytic hierarchy process and the fuzzy evaluation method [29]. e essence of the analytic hierarchy process is a way of decision-making thinking.…”
Section: Fuzzy Analytic Hierarchy Processmentioning
confidence: 99%
“…e deflection equation of the thin plate rock mass with both sides simply supported (S-S) along the x direction could be expressed as follows [46][47][48]: e boundary conditions of the thin plate rock mass with both free sides (F-F) along the y direction may be as follows:…”
Section: Deflection Equation Of the In Plate Rock Mass S-f-s-f Under ...mentioning
confidence: 99%